Cotton and its Relation With Gossypol - A Irawan Sutikno (Indonesian Center for Animal Research and Development, 2000)
Suitable weather is a major problem for cotton field plantation in Indonesia. In one side it needs water for growing up, on the contrary, absolute dry situation for flowering and harvesting is necessary. Therefore, cotton contribution is remarkably small (1 percent from local product) but it can be expected to increase with a new location area in the future. Although cotton ball is the main product, cotton seed becomes the by-product, which can be processed to cotton oil and its left over called cotton seed meal. The seeds contain gossypol, a toxic pigment, which found in its oil and the meal. Gossypol becomes an important factor to be noticed since the meal contains high protein, which can be used as a foodstuff. In a certain concentration, poultry and pigs can not tolerate the compound. In advance countries, oil extraction is the best way to remove gossypol, but the process is considered expensive. There is a need for alternative ways to remove it. Key words : Cotton, gossypol, detoxification